1995
DOI: 10.1021/bi00004a029
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Protein Geranylgeranyltransferase-I: Substrate Specificity, Kinetic Mechanism, Metal Requirements, and Affinity Labeling

Abstract: Protein geranylgeranyltransferase-I (PGGT-I) catalyzes the transfer of the 20-carbon prenyl group from geranylgeranyl pyrophosphate to the cysteine residue near the C-termini of a variety of eukaryotic proteins. Kinetic analysis of homogenous PGGT-I from bovine brain reveals that the reaction follows a sequential pathway in which either prenyl donor or acceptor can bind first to the enzyme and that the reaction operates at steady-state rather than at rapid equilibrium. Substrate inhibition by prenyl acceptor b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
125
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(143 citation statements)
references
References 31 publications
16
125
2
Order By: Relevance
“…Using a gel-filtration assay we showed that RabGGTase forms a stable complex with Rab7±REP-1 in the absence of the lipid substrate GGpp. This is consistent with the findings that GGTase I and farnesyl transferase can form a stable complex with both protein and lipid substrate independently [9,11]. Formation of the stable complex was dependent on the presence of both Rab7 and REP-1, supporting the notion that Rab7 could be recognized by RabGGTase only in its complex with REP-1.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Using a gel-filtration assay we showed that RabGGTase forms a stable complex with Rab7±REP-1 in the absence of the lipid substrate GGpp. This is consistent with the findings that GGTase I and farnesyl transferase can form a stable complex with both protein and lipid substrate independently [9,11]. Formation of the stable complex was dependent on the presence of both Rab7 and REP-1, supporting the notion that Rab7 could be recognized by RabGGTase only in its complex with REP-1.…”
Section: Discussionsupporting
confidence: 91%
“…The choice between farnesylation and geranylgeranylation is determined by the hydrophobicity of the X residue [7]. Original studies suggested that the prenylation reaction catalyzed by farnesyl transferase or GGTase I proceeds via a random sequential mechanism by which the enzyme can bind the protein and lipid substrates independently [8,9]. However, recent studies with human and yeast farnesyl transferase supported an ordered addition of substrates [10,11].…”
mentioning
confidence: 99%
“…Previous kinetic data suggest that the kinetic scheme for GGTase I is similar to that of FTase (34,35), including that the substrate binding is functionally ordered with GGPP binding before peptide and that the rate constant for geranylgeranylation is faster than product dissociation (Scheme 1). The kinetic and thermodynamic data that we have determined for GGTase I are consistent with this basic kinetic mechanism.…”
Section: Resultsmentioning
confidence: 98%
“…Interestingly, the Mg(II) dependence of GGTase I is not well understood. Initial studies indicated that, similar to FTase, GGTase I required Mg(II) for maximal activity (33,34). However, later studies demonstrated that metal-chelating reagents have little effect on the steadystate turnover rate of GGTase I, suggesting that Mg(II) is not required for maximal activity (35).…”
mentioning
confidence: 99%
“…Protein prenyltransferases preferentially operate via an ordered mechanism for binding two substrates with the prenyl pyrophosphate substrate binding first [2,5,6]. Mammalian PGGT-I and PFT form a tight complex selectively with their substrates, geranylgeranyl pyrophosphate (GGPP) and farnesyl pyrophosphate (FPP), respectively [7,8].…”
Section: Introductionmentioning
confidence: 99%